Job satisfaction of female employees in microfinance institutions of Bangladesh - Uddin, Md Nazim; Hamdan, Hamdino; Che Embi, Nor Azizan; Kassim, Salina; Md Saad, Norma (2019)
The purpose of this study is to examine the level of female employee satisfaction regarding their job of microfinance institutions in Bangladesh. Moreover, it focuses on the various factors that influence female employee job satisfaction of microfinance institutions. The study utilised quantitative research methods, and use Herzberg’s motivation-hygiene theory (19590. A total of 24 structured questionnaires with five dimensions have been given to 100 female respondents of selected microfinance institutions in Bangladesh. The findings reveals some variables (performance-based salary increment, available opportunities for promotion, satisfaction on job environment, colleagues help during huge workload, opportunity to interact with other employees on a formal level, use of skill, experience & qualification, recognition for good work, and learning opportunity) have significant impact on female employee satisfaction to the microfinance institutions. The limitation of the studied investment fund is that it invests in expanding and mature microfinance institutions (MFIs). So the results of this research can only be generalised to expanding and mature MFIs. This study aims at contributing for better female employees job satisfaction of the MFIs given that it has strong implications on financial benefit, work environment, job security, decision making, training and resources of the MFIs.